Sustainable real estate in the developing world - Abdulai, Raymond Talinbe; Baffour Awuah, Kwasi Gyau (Emerald Publishing Limited, 2021)
Many years have elapsed since the start of sustainability revolution, yet there is still a lack of diverse collections offering in-depth analysis of sustainability principles applied to real estate in the developing world. Sustainable Real Estate in the Developing World offers a perfect and ideal synthesis of works that examine sustainability within various facets of real estate and urban development in the developing world. Harnessing multi- and inter-disciplinary perspectives, this book discusses the fundamental issues of the complex nexus between the built environment and sustainable development, thereby illuminating how they are affecting and will potentially affect each other. The book highlights rich and practical experiences, challenges, and best practices of over ten countries in four continents, with contributors proffering solutions around topics such as the following: sustainable development goals and the urban agenda; housing development in the context of environmental sustainability; demand for sustainable features in commercial real estate; urban development, land use changes, and environmental impacts in cities; urbanization, environmental externalities, and house prices; building information modelling adaptability for sustainable residential real estate development; and COVID-19 and sustainable development. This collection is useful to academics, researchers, and students in all the built environment disciplines, as well as to policy makers, practitioners, professional bodies and the international donor community.